The Work Gratitude Scale: Development and Evaluation of a Multidimensional Measure - Youssef-Morgan, Carolyn M.; van Zyl, Llewellyn E.; Ahrens, Barbara L. (Frontiers in Psychology, 2022)
This study explores gratitude as a multidimensional and work-specific construct. Utilizing a sample of 625 employees from a variety of positions in a medium-sized school district in the United States, we developed and evaluated a new measure, namely the Work Gratitude Scale (WGS), which encompasses recognized conative (intentional), cognitive, affective, and social aspects of gratitude. A systematic, six-phased approach through structural equation modeling was used to explore and confirm the factorial structure, internal consistency, measurement invariance, concurrent, convergent and discriminant validity of the WGS. The results supported a 10-item measure with three dimensions: “grateful appraisals” (3 items), “gratitude toward others” (4 items), and “intentional attitude of gratitude” (3 items). Thereafter, first-order, second-order, and bifactor confirmatory models were estimated and compared. Work gratitude was found to be best described by a second-order construct with three underlying first-order dimensions. Measurement invariance was supported in relation to gender. Concurrent validity was supported in relation to two existing dispositional gratitude scales, namely the Gratitude Questionnaire and the Gratitude, Resentment and Appreciation Scale. Convergent validity was supported in relation to the Core Self-Evaluations Scale and the Psychological Capital Questionnaire. Discriminant validity was supported in relation to various demographic factors such as age, gender, occupation and tenure. The findings support the WGS as a multidimensional measure that can be used in practice to measure overall work-related gratitude and to track the effectiveness of gratitude-related workplace interventions.